Polarity-preserved diffraction extracting method using modified apex-shifted Radon transform and double-branch Radon transform. (18th June 2018) - Li, Chuangjian; Peng, Suping; Zhao, Jingtao; Cui, Xiaoqin; Du, Wenfeng; Satibekova, Sandugash
Abstract: The localization of diffractors is a great challenge for seismic data with a low signal to noise ratio, and it is also difficult to preserve the polarity characteristics of edge diffracted waves in the separated diffractions. In this paper, we present a method to locate the diffraction points and extract the diffractions from reflected data by using the Hilbert transform, the modified apex-shifted Radon transform (ASRT) and double-branch Radon transform. The Hilbert transform is used to weaken the impact of dominant reflection amplitude on detecting weaker diffractions in instantaneous phase data. The modified ASRT and double-branch Radon transform are applied to locate the apex of diffractions and preserve the polarity reversal of edge diffracted waves emitted from reflector discontinuities, respectively. The synthetic and real data applications illustrate that the method not only accurately locate the diffraction apices but also discriminate the responses of the small-scale scattering objects and the reflector edges.